Do Tanzanian Companies Practice Pecking Order Theory, Agency Cost Theory or Trade-Off Theory? An Empirical Study in Tanzanian Listed Companies - Ntogwa Ng'habi Bundala (International Journal of Economics and Financial Issues, 2012)
The empirical study was focused predominantly on validity tests of the three theories on capital structures, the static trade-off theory, the pecking order theory (information asymmetry theory), and agency cost theory in the Tanzanian context. The study used secondary data from eight of the non-financial companies listed in Dar Es Salaam Stock Exchange (DSE) from 2006-2012. The study used descriptive (quantitative) approach to test the practicality of the theories in Tanzania. The multiple regressions model used to test the theoretical relationship between the financial leverage and characteristics of the company. The research found that there is no strong evidence for validation of static trade off theory, little support of pecking order theory, but the agency cost theory is confirmed to be valid and practiced in Tanzania. It recommended that Tanzanian companies should be adhering to the determinants of the capital structure in the Tanzanian context found by this study.